Ethical Challenges Confronting Accounting Professionals in Contemporary Business (gjstudies, 2014)
This research paper investigates the evolving and increasingly complex ethical landscape faced by accounting professionals in the modern business environment. Movingbeyond traditional discussions of fraud and compliance, this study employs a novel, tripartite analytical framework that synthesizes principles from virtue ethics, systems theory, andbehavioral economics to diagnose ethical challenges. The methodology involves a qualitative meta-analysis of documented ethical dilemmas from 1995 to 2004, coupled witha proprietary scenario-based simulation administered to a stratified sample of 150 certified public accountants. The analysis reveals that contemporary ethical challenges are lessabout blatant malfeasance and more frequently arise from systemic pressures, ambiguousincentive structures, and cognitive biases exacerbated by technological acceleration andglobalization. A key original finding is the identification of ’latent ethical drift’—a gradualnormalization of questionable practices driven by competitive and operational pressures,rather than explicit malicious intent. The results demonstrate that standard compliancebased training is insufficient to address these nuanced challenges. The paper concludesby proposing a new, resilience-oriented model for accounting ethics education and firmculture, emphasizing ethical foresight and systemic awareness. This contribution is significant for its interdisciplinary approach and its focus on the emergent, systemic nature ofethical threats in the digital age, offering a fresh perspective for both academic discourseand professional practice.